Optimalisasi Peran Pusat Informasi dan Pemanduan DalamMeningkatkan Kualitas Pelayanan Kebun Raya Bogor - Musthofa, Budiman Mahmud; Priyanto, Priyanto; Putri, Elissya Nuriva (UI Scholars Hub, 2017)
Quality of service is one of the key in hospitality industry, one of which is service in a tourism object. This article discusses the optimization role of information center and gudiing in improving service quality at Bogor Botanical Garden (KRB). Through qualitative methods, the results of this study showed that the role of information center and guiding KRB in disseminating information aboutbotanical garden to the visitors plays a very important role that increases the number of tourists who come. Based on the analysis of five dimensions of excellent service, then in general has fulfilled all the dimensions of service in KRB, the dimensions of Reliability, Assurance, Tangibles, Empathy, and Responsiveness. Suggestions that can be given in this study is the need to improve the quality of human resources and human res